Diets Alter the Gut Microbiome of Crocodile Lizards - Jiang, Hai-Ying; Ma, Jing-E; Li, Juan; Zhang, Xiu-Juan; Li, Lin-Miao; He, Nan; Liu, Hai-Yang; Luo, Shu-Yi; Wu, Zheng-Jun; Han, Ri-Chou; Chen, Jin-Ping (Frontiers in Microbiology, 2017)
The crocodile lizard is a critically endangered reptile, and serious diseases have been found in this species in recent years, especially in captive lizards. Whether these diseases are caused by changes in the gut microbiota and the effect of captivity on disease remain to be determined. Here, we examined the relationship between the gut microbiota and diet and disease by comparing the fecal microbiota of wild lizards with those of sick and healthy lizards in captivity. The gut microbiota in wild crocodile lizards was consistently dominated by Proteobacteria (~56.4%) and Bacteroidetes (~19.1%). However, the abundance of Firmicutes (~2.6%) in the intestine of the wild crocodile lizards was distinctly lower than that in other vertebrates. In addition, the wild samples from Guangdong Luokeng Shinisaurus crocodilurus National Nature Reserve also had a high abundance of Deinococcus-Thermus while the wild samples from Guangxi Daguishan Crocodile Lizard National Nature Reserve had a high abundance of Tenericutes. The gut microbial community in loach-fed crocodile lizards was significant different from the gut microbial community in the earthworm-fed and wild lizards. In addition, significant differences in specific bacteria were detected among groups. Notably, in the gut microbiota, the captive lizards fed earthworms resulted in enrichment of Fusobacterium, and the captive lizards fed loaches had higher abundances of Elizabethkingia, Halomonas, Morganella and Salmonella, all of which are pathogens or opportunistic pathogens in human or other animals. However, there is no sufficient evidence that the gut microbiota contributes to either disease A or disease B. These results provide a reference for the conservation of endangered crocodile lizards and the first insight into the relationship between disease and the gut microbiota in lizards.